Contemporary Perspectives On The Impact Of Enzymatic Dysfunction In The Pathogenesis Of Female Infertility And Innovative Approaches To Its Treatment (Literature Review) - Ernazarova S.I; Shukurov F.I (Zien Journals, 2024)
To conduct a comprehensive analysis of modern aspects of enzymatic dysfunction in female infertility and to explore innovative methods for its correction
Keywords: innovative; comprehensive; modern